Pengaruh Literasi Zakat, Religiusitas dan Lingkungan Sosial terhadap Minat Berzakat Masyarakat (Studi kasus Masyarakat Kelurahan Anduring Kecamatan Kuranji kota Padang) - Cici Pratiwi; Ingra Sovita (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
Zakat is an important economic instrument in Islam that plays a significant role in improving social welfare and reducing poverty. Indonesia has great potential in zakat collection, but the realization of zakat funds is still not optimal, including in Padang City. In Anduring Village, Kuranji District, the high potential of zakat has not been followed by a high level of public interest in paying zakat through official institutions. This condition is influenced by several factors, including zakat literacy, religiosity, and social environment.This study aims to analyze the effect of zakat literacy, religiosity, and social environment on the interest in paying zakat among the community. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 260 respondents using purposive sampling technique. The data were analyzed using Structural Equation Modeling – Partial Least Square (SEM-PLS) with SmartPLS software.The results show that zakat literacy, religiosity, and social environment have a significant effect on the interest in paying zakat. Higher understanding of zakat, stronger religiosity, and supportive social environment will increase the community’s intention to pay zakat through official institutions.